AWAKENING THE TRUE SELF: THE TRANSFORMATIVE POWER OF MYSTICAL TRADITION IN PAULO COELHO’S THE ZAHIR - K. P., SreeLekshmi; S., Sreelatha (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The mystical tradition often rooted in ancient wisdom and spiritual practices draws its influence from various mystical elements, notably Sufism and other esoteric traditions. The novel, The Zahir delves into spiritual elements, self-discovery and interconnectedness of individuals offering a mystical journey that grows beyond the surface of everyday life. The novel is about the story of a renowned author whose wife had disappeared under mysterious circumstances. It describes the search for her from South America to Spain, France ending in Central Asia. The journey leads him to a new understanding of the nature of love, the power of destiny. Paulo Coelho wrote The Zahir while he was making his own pilgrimage through the world in between January and June 2004. The concept of forgetting personal history is one of the main concepts of the novel and it is a part of many initiation of tradition which is closely tied to the idea of embracing the present and future without being burdened by past mistake or regrets. This paper attempts to analyse how the influence of mysticism helps to shape the true self of the main character in the novel, The Zahir.